La théorie du sous-emploi urbain dans les pays en voie de développement - Mazumdar, Dipak (L'Actualité économique)

(untitled) (HEC Montréal, 1977)
AbstractThe article investigates the working of a model of an urban labor market in LDG's which has two sectors—one sector (the U-sector) being characterized by ease of entry, variable hours of work and flexible earnings, the other (the O-sector), by rigid wages maintained at a relatively high level. Migrants from the rural areas respond to the expected earnings in both sectors, and can search for O-sector jobs while participating in the U-sector. Labor supply determined by such a migration function, together with the relative rates of growth of income in the two urban sub-sectors (on plausible assumptions) lead to the possibility that average earnings in the U-sector decline over time relative not only to O-sector wage, but also to the alternative income in the rural sector. In the last section a distinction made between two types of job seekers found in the U-sector—those with and those without an interest in the O-sector—gives the result that average earnings in the U-sector may sometimes be independent of conditions in the O-sector. It is also seen that, under certain conditions, even with ease of entry and variable hours of work, the U-sector may not serve as a channel for migrants seeking to enter the O-sector. The analysis provides a classification of labor market types which may be of help in organizing empirical information from different parts of the world.